LEADING THEORIES IN AKWA IBOM COLONIAL HISTORIOGRAPHY - Edet Efiong Okon (International Studies Journal)
As applicable in other part of Africa, the imposition of colonialism hindered development and sustainability of the indigenous Akwa Ibom socio-cultural, economic and political institutions as such institutions were labelled negatively to justify the merits of the colonial system. European scholars, missionaries, historians and scientists were dislodged to perfect Britain's ambitions in Akwa Ibom area through various ideological and pseudo-scientific postulations. The study employed mostly secondary sources to attempt a historical analysis of colonial theories adopted in the historiography of Akwa Ibom past and history. Such denigrating terms such as primitive, heathen, pagan and illicit among others were applied to explain the people's uncivility. This research is an attempt to unveil the fact that the area now refers to as Akwa Ibom had adversely been affected by the various Eurocentric theories and ideologies aimed at destabilizing her indigenous identify and peoplehood up to the post- colonial era.